2014
DOI: 10.1111/adb.12171
|View full text |Cite
|
Sign up to set email alerts
|

Lower subcortical gray matter volume in both younger smokers and established smokers relative to non‐smokers

Abstract: Although established adult smokers with long histories of nicotine dependence have lower neural tissue volume than non-smokers, it is not clear if lower regional brain volume is also observed in younger, less established smokers. The primary goal of this study was to investigate neural tissue volume in a large group of smokers and non-smokers, with a secondary goal of measuring the impact of age on these effects. We used voxel-based morphometry to compare regional gray matter volume in 118 individuals (59 smok… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
84
2
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(94 citation statements)
references
References 42 publications
6
84
2
1
Order By: Relevance
“…It remains unclear whether structural and functional differences among smokers reflect the effects of chronic exposure to toxic compounds found in combustible tobacco on neurovasculature, 51 are a product of epigenetic changes 52 or neuroplasticity 53 following chronic nicotine use, or reflect a smoking endophenotype with impaired inhibitory control of behavior. Therefore, despite controlling for a number of variables known to affect GMV and neurocognition, longitudinal studies are needed that examine the effects of smoking/nicotine across development and following smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear whether structural and functional differences among smokers reflect the effects of chronic exposure to toxic compounds found in combustible tobacco on neurovasculature, 51 are a product of epigenetic changes 52 or neuroplasticity 53 following chronic nicotine use, or reflect a smoking endophenotype with impaired inhibitory control of behavior. Therefore, despite controlling for a number of variables known to affect GMV and neurocognition, longitudinal studies are needed that examine the effects of smoking/nicotine across development and following smoking cessation.…”
Section: Discussionmentioning
confidence: 99%
“…Few studies have examined grey matter differences in young adult smokers, although one previous study reported that younger smokers had significantly lower grey matter volume in the left thalamus and the left amygdala than their non-smoking peers (Hanlon et al, 2014). Moreover, previous structural studies mainly focused on adult smokers and typically used voxel-based morphometry (VBM), which revealed reduced grey matter volume/density in several brain regions, e.g., prefrontal cortex (PFC), orbitofrontal cortex (OFC), anterior cingulate cortex (ACC), insula, cerebellum, thalamus, and temporal/occipital lobe, including the parahippocampal gyrus (Brody et al, 2004;Fritz et al, 2014;Gallinat et al, 2006;Zhang et al, 2011aZhang et al, , 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…There has also been a report of actual increase in the volume of the putamen in smokers [81]. However, there have also been reports of decreased gray matter [34] and increased white matter [36] in the putamen of smokers. Several studies have shown that chronic smoking is associated with reduced gray matter in the medial frontal cortex [31, 32].…”
Section: Discussionmentioning
confidence: 99%
“…Conflicting findings have been reported in the cerebellum and basal ganglia [3238]. For example, in the basal ganglia there have been reports of total volume increases [38], increased [32] and decreased [34] gray matter volume, and increased white matter volume [36]. Further work is necessary to clarify these findings, but it is clear that smoking is associated with anatomical changes in the frontal lobes, basal ganglia, and cerebellum.…”
Section: Introductionmentioning
confidence: 99%